Menjadi Jemaat Publik - Pattianakotta, Hariman (Theologia in Loco, 2021)
Abstract Being church in the world is a way of life for church that is determined by its DNA and Godâ€™s design. This article offers the metaphor for a church in the world called "public congregation." It is characterized by three dimensionsâ€”missional, relational, and incarnational. This article uses Joas Adiprasetya's concept of perichoresis in conversation with Leonard Sweet's thoughts on the missional, relational, and incarnational (MRI) church. The conversation is further extended to include the metaphoric approach by Donald Messer to argue for the relevance of public congregation as a metaphor for church life and orientation toward the world. Keywords: Public congregation, church, missional, relational, incarnational, public space Abstrak Panggilan menjadi jemaat publik merupakan jalan hidup menggereja yang sesuai dengan DNA dan desain Allah atas gereja di dalam dunia. Karena itu, dalam artikel ini, saya menawarkan metafora â€œjemaat publikâ€ bagi jemaatjemaat untuk menerjemahkan dirinya sebagai gereja yang misional, relasional, dan inkarnasional dalam ruang publik. Untuk menjelaskan tawaran ini, saya akan mengurai pandangan mengenai gereja dan dunia dalam bingkai trinitasperikhoresis dari Joas Adiprasetya dan mengelaborasi pemikiran Leonard Sweet mengenai gereja yang misional, relasional, dan inkarnasional (MRI). Kemudian saya akan membaca jemaat dari perspektif ekologis dalam studi-studi kongregasi, lalu dengan pendekatan metaforik dari Donald Messer, saya akan mendialogkan pemikiran Adiprasetya dan Sweet untuk menawarkan konstruksi saya mengenai jemaat publik. Kata-kata Kunci: Jemaat publik, gereja, misional, relasional, inkarnasional, ruang publik